Observations of babies in the context of an internship (Olhar de Professor, 2019)
Investigations involving the study of infants have been growing in Brazil. It aims to point out somecharacteristics of the education of the babies, among them. The methodology of observation is used. The centralcharacteristics of this education, with babies, found in the research are: we have a pedagogical practice in whichthe teachers do not encourage and promote the interaction between the babies and a partial autonomy of these in theplanned activities; the interactions through the games still do not reach the proposal of the theory of the exchangesbetween babies of Mira Stambak and his team - referential of this research. And finally, actions with babies aredefined and directed by the adult. Taken together, these findings demand a new “das” look and practices, as wellas in relation to the production of knowledge in this theme. In this sense, the present work is characterized as areferential enhancer for other researches, on infants, in Brazilian contexts and of Internship, in Pedagogy courses
Keywords: Internship. Babies. Pedagogical practices.